1997
DOI: 10.1111/j.1349-7006.1997.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Development of N, N′‐Dimethylhydrazine‐induced Rat Colonic Aberrant Crypt Foci by Pre, Post and Simultaneous Treatments with 24R,25‐Dihydroxyvitamin D3

Abstract: It has recently been reported that new vitamin D3 derivatives can exert inhibitory effects on colon carcinogenesis in rats. In the present study the chemopreventive potential of 24R,25‐dihydroxyvitamin D3 (24ff,25(OH)2vitainin D3) was assessed in a murine model of colon carcinogenesis. In experiment 1, male 6‐week‐old F344 rats were administered N2N‐dimethylhydrazme (DMH) 20 mg/kg s.c. once a week 4 times. The rats were fed 24R,25(OH)2vitaniin D3 at 10 ppm in the diet prior to (pre), together with (simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…PhIP is known to induce ACF in different strains of rats in a dosedependent manner, 28 but to a much lower degree than azoxymethane (AOM) 29 or dimethylhydrazine (DMH). 30 Furthermore, lowdose potential of PhIP on the induction of ACF has already been described by Fukushima et al 31 In the present study, the particular focus was on the pathologic examination of practical effects of PhIP at low doses mimicking human exposure levels. For this purpose, we adopted a 2-stage carcinogenesis model featuring initiation with AOM to gain an appreciable tumor yield in the large intestine for quantitative analysis using tumors as endpoints.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…PhIP is known to induce ACF in different strains of rats in a dosedependent manner, 28 but to a much lower degree than azoxymethane (AOM) 29 or dimethylhydrazine (DMH). 30 Furthermore, lowdose potential of PhIP on the induction of ACF has already been described by Fukushima et al 31 In the present study, the particular focus was on the pathologic examination of practical effects of PhIP at low doses mimicking human exposure levels. For this purpose, we adopted a 2-stage carcinogenesis model featuring initiation with AOM to gain an appreciable tumor yield in the large intestine for quantitative analysis using tumors as endpoints.…”
mentioning
confidence: 57%
“…4 crypts) as described previously. 30 For the quantitative analysis, the mucosal area (cm 2 ) of each colonic segment was measured with the aid of a color video image processor (IPAP; Sumica Technos, Osaka, Japan) and all ACF data were expressed as numbers/cm 2 . Thereby, 5 rats were omitted from the effective numbers because colonic areas could not be measured accurately mainly due to perforation.…”
Section: Acf Analysismentioning
confidence: 99%
“…In the case of the 24R,25-dihydroxyvitamin D 3 analog, studies using rats with chemically induced colonic aberrant crypt foci (early signs of colon cancer) or glandular stomach cancer have suggested that this analog exerts chemopreventive effects (264,265). No rise in serum calcium was seen in former study, but urinary calcium levels were found to be markedly increased in the treated animals, indicating that 24R,25-dihydroxyvitamin D 3 have a narrow therapeutic window.…”
Section: Other Analogs Of Interestmentioning
confidence: 93%
“…Iseki and Kobayashi [43] found signifi cantly reduced gastric hyperplasia and adenocarcinoma and decreased multiplicity in MNNG-challenged animals. Administration of this analogue during or after dimethylhydrazine challenge showed reduced ACF formation and PCNA index in both cases, but it was more marked in the postchallenge group [44]. A complex set of experiments looked at the effects of 24R,25(OH) 2 D 3 on a time point-sensitive, multicarcinogen, multiorgan study of colon cancer in rats [45].…”
Section: Metabolite Analoguesmentioning
confidence: 98%